2019
DOI: 10.1108/qrfm-12-2017-0125
|View full text |Cite
|
Sign up to set email alerts
|

Greenwashing and responsible investment practices: empirical evidence from Zimbabwe

Abstract: Purpose This paper aims to explore the nature of responsible investment (RI) practices in Zimbabwe from the point of view of the institutional asset owners by investigating not only how they incorporate the ESG criteria when selecting investee companies but also the elements of greenwashing and impression management. Design/methodology/approach Based on semi-structured interviews conducted with Pension Fund Entities, Mutual Funds and Life Assurance companies, the authors used interpretive methodological appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…In the past few years, Sustainable Finance has become a buzzword in the financial sector, being portrayed as a powerful leverage to fight climate change (GSI Alliance, 2019). However, in some instances, the investment strategies and pervasive advertisement of seemingly ‘new and green’ investment products in the industry have been criticized by activists, scholars and policy makers for ‘greenwashing’ (Dupre and Roa, 2020; Hellsten and Mallin, 2006; Olatubosun and Nyazenga, 2019). Given the crucial role that financial news and journalists play in providing a forum for discussion, information and critique about this trend, this study sought to understand how journalists from six countries in Europe (AT, BE, CH, DE, NL, UK) describe their daily journalistic practices and how they perceive their journalistic role when covering SF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few years, Sustainable Finance has become a buzzword in the financial sector, being portrayed as a powerful leverage to fight climate change (GSI Alliance, 2019). However, in some instances, the investment strategies and pervasive advertisement of seemingly ‘new and green’ investment products in the industry have been criticized by activists, scholars and policy makers for ‘greenwashing’ (Dupre and Roa, 2020; Hellsten and Mallin, 2006; Olatubosun and Nyazenga, 2019). Given the crucial role that financial news and journalists play in providing a forum for discussion, information and critique about this trend, this study sought to understand how journalists from six countries in Europe (AT, BE, CH, DE, NL, UK) describe their daily journalistic practices and how they perceive their journalistic role when covering SF.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that the ESG criteria commonly used to identify sustainable investments in the financial industry are understood and interpreted very differently, with different outcomes (Berg et al, 2020), and with limited levels of trustworthiness perceived among investors (Paetzold et al, 2015). More recently, Olatubosun and Nyazenga (2019) pointed out that responsible investment practices are used as a symbolic marketing tool in Zimbabwe. Furthermore, an analysis by the non-profit think tank, 2 Degrees Investing Initiative, found that 85% of funds with a green theme in Europe make 'unsubstantiated and misleading impact-related claims that violate existing market regulations' (Dupre and Roa, 2020: 4).…”
Section: Sustainable Finance Greenwashing and The Role Of The Financial Pressmentioning
confidence: 99%
“…This explains the need for an industry-wide non-competitive collaboration to develop technologies that could be shared by many in the industry. Conversely, the non-specification of the measurement criteria of the scientific targets may encourage greenwashing and impression management which has plagued financial and corporate report world for quite a while now (see Solomon et al, 2013;Olatubosun and Nyazenga, 2019). The organisers of the "Fashion Pact" have however promised to publish how they meet the annual scientific targets through the Boston Consulting Group (BCG), but how they will source the data remains unclear.…”
Section: Measuring Performance In the Sustainability Environmentmentioning
confidence: 99%
“…What is more, an analysis by the "2 Degrees Investing Initiative" found that 85% of green themed funds make "unsubstantiated and misleading impact-related claims that violate existing market regulations" (Dupre and Roa 2019, 4), and Olatubosun and Nyazenga (2019) have found responsible investment practices in Zimbabwe being used as a symbolic marketing tool. These recent findings are in line with past criticism that has been raised by various scholars and experts with regard to sustainable and responsible investments for its lack of transparency (Schrader 2006), data availability and reporting (Ferrua Rotaru 2019), diverging definitions (Paetzold, Busch, and Chesney 2015), or inconsistent measurements of ESG ratings (Berg, Kölbel, and Rigobon 2020), and more recently a dilution of regulation of SF products on the European level (Webb 2021).…”
Section: Literature Reviewmentioning
confidence: 99%